BANK CONTRACTS IN THE NEW ROMANIAN CIVIL CODE - DAN VELICU (Challenges of the Knowledge Society, 2012)
The adoption of the new Civil Code and its entry into force on October 1st 2011 has involved an extensive reform of the private law. The new Code, as its authors notice, has aimed primarily to achieve a unification of the private law, the largest part of the land commerce regulations from the commerce code adopted in 1887 being absorbed into the new text and, secondly, to harmonize the basic institutions of the private law with the European regulations and directives. Beyond these two major objectives, the new Civil Code comprises regulations with innovative character compared to the Romanian law, such as bank contracts. This study is preliminary and aims to highlight the inspiring models of the new Civil Code and to analyse the functionality of the newly used concepts.